2023
DOI: 10.3390/land12040769
|View full text |Cite
|
Sign up to set email alerts
|

The Spreading of Antibiotic-Resistant Bacteria in Terrestrial Ecosystems and the Formation of Soil Resistome

Abstract: Terrestrial ecosystems play a crucial role in the formation of soil resistome and the spread of antibiotic-resistant bacteria. Comprehensive studies of soil microbial communities, their structure, integrity, and level of antibiotic resistance (AR) in various terrestrial ecosystems were conducted. In total, 389 strains of dominant bacteria were isolated from the studied ecosystems, 57 of which were resistant to antibiotics, with levels of antibiotic resistance exceeding 70%. The soil microbiome of primeval fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The study also revealed that Pantoea agglomerans and Bacillus cereus showed the highest levels of resistance. Approximately 23% of the isolated bacteria exhibited resistance to antibiotics [ 50 ]. Among all classes of ARGs found in wastewater samples worldwide, tet genes exhibited the highest detection frequency, with researchers identifying approximately 20 different types of tet genes in wastewater [ 51 ].…”
Section: Antibiotic Resistance In Environmentmentioning
confidence: 99%
“…The study also revealed that Pantoea agglomerans and Bacillus cereus showed the highest levels of resistance. Approximately 23% of the isolated bacteria exhibited resistance to antibiotics [ 50 ]. Among all classes of ARGs found in wastewater samples worldwide, tet genes exhibited the highest detection frequency, with researchers identifying approximately 20 different types of tet genes in wastewater [ 51 ].…”
Section: Antibiotic Resistance In Environmentmentioning
confidence: 99%
“…Usually, microbial biomass responds more promptly to management practices compared to the total organic carbon content in the soil [51][52][53]. It is known that microbial biomass is an important indicator in assessing the ecological status of ecosystems, as well as a sensitive indicator for the influence of applied agricultural technologies and fertilizers [54][55][56]. The microbiological analysis of soil from the selected agroecosystems, where blueberries were cultivated with the addition of SMS and peat, yielded notable results as can be observed in Table 4.…”
Section: Additive To the Soil For Blueberry Cultivationmentioning
confidence: 99%
“…It serves as a sink and source for various elements, such as carbon (C), nitrogen, and phosphorus. These elements are essential for the functioning of biological processes and are recycled through soil microorganisms, plants, and other organisms in the ecosystem ( Gomiero, 2016 ; Demyanyuk et al, 2020 ; Gomes et al, 2023 ; Symochko et al, 2023 ). In particular, soil plays a pivotal role in the destructive chain of the C cycle and its sequestration (or deposition), thereby influencing climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Since biological indicators of soil quickly respond to natural and anthropogenic factors, they are widely used in monitoring studies, to assess soil health, and to develop environmentally safe agricultural technologies ( Rinot et al, 2019 ; Symochko et al, 2021b , 2023 ; Bhaduri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%